Validations of the Brazilian version of the Early Childhood Oral Health Impact Scale (ECOHIS) Validação da versão brasileira do Early Childhood Oral Health Impact Scale (ECOHIS) - Paulo Antônio Martins-Júnior; Joana Ramos-Jorge; Saul Martins Paiva; Leandro Silva Marques; Maria Letícia Ramos-Jorge (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This study aimed to evaluate the psychometric properties of the Brazilian version of the Early Childhood Oral Health Impact Scale (ECOHIS). A total of 247 children aged 2 to 5 years and their parents/guardians participated in this study. A clinical oral examination was performed and the parents/guardians completed the ECOHIS questionnaire. Within a period of four-weeks, 20% of the participants repeated the ECOHIS questionnaire. Construct validity was determined using Spearman's rank correlation. Discriminant validity, internal consistency and test-retest reliability were also evaluated. The children were divided into 2 groups: group 1 (with dental caries) and group 2 (caries-free). Children with caries showed higher mean ECOHIS scores than the caries-free children. The child impact section (p < 0.01), family impact section (p < 0.01) and total ECOHIS scores (p < 0.01) were significantly correlated with tooth decay. Cronbach's alpha coefficients demonstrated satisfactory internal consistency. The Brazilian version of the ECOHIS is a valid instrument for assessing oral health-related quality of life in preschool children with Brazilian Portuguese-speaking primary caregivers. O objetivo deste estudo foi avaliar as propriedades psicométricas da versão brasileira do Early Childhood Oral Health Impact Scale (ECOHIS). Duzentas e quarenta e sete crianças de 2 a 5 anos e seus pais/cuidadores foram convidados a participar. Foi realizado exame clínico bucal e os pais completaram o ECOHIS. Após quatro semanas, 20% dos participantes responderam ao ECOHIS pela segunda vez. A validade de construto foi determinada através da correlação de Spearman. A validade discriminante, consistência interna e confiabilidade teste-reteste foram avaliadas. As crianças foram divididas em dois grupos: grupo 1 (com cárie) e grupo 2 (sem cárie). As crianças com cárie tinham maiores escores médios do ECOHIS do que as crianças sem cárie. Os domínios impacto na criança (p < 0,01), impacto na família (p < 0,01) e escores totais ECOHIS (p < 0,01) foram significativamente correlacionados com dentes cariados. Coeficientes alfa de Cronbach demonstraram consistência interna satisfatória. A versão brasileira do ECOHIS é apropriada para a avaliação da qualidade de vida relacionada à saúde bucal em crianças pré-escolares de pais cuja língua primária seja o português.